PERUBAHAN PARADIGMA DALAM ORGANISASI BELAJAR DI ABAD 21 - Fakhruddin, M; Ananda, Rusydi; Istiningsih, Siti (Perspektif Ilmu Pendidikan, 2013)
The fast development of advance science and technology in the twentieth century has forced the people to change and adjust their ways of thinking and acting. Any society or nation does not adjust themselves to the changes around them will be left behind and isolated. As the effect of the radical changes, the social and commercial organizations are demanded to change to be able to survive and develop. The problem is how to manage and lead the organizations properly applying the new paradigm of the twentieth century. This article critically discusses the paradigm shift in the twentieth century resulted by the fast development of science and technology and in the other side it brought some problems such as borderless nations or globalization. The deductive and inductive analysis of the problems in this article concludes that educational organizations in particular should be proactive and absorb the positive changes occurring in their environment and in the world. Management and leadership within the educational institution should be based on the learning organization principles to survive, develop, and complete.